Efficacy and safety of strong opioids for chronic noncancer pain and chronic low back pain: a systematic review and meta-analyses. Issue 4 (28th April 2022) - Nury, Edris; Schmucker, Christine; Nagavci, Blin; Motschall, Edith; Nitschke, Kai; Schulte, Erika; Wegwarth, Odette; Meerpohl, Joerg J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: In recent years, long-term prescribing and use of strong opioids for chronic noncancer pain (CNCP) has increased in high-income countries. Yet existing uncertainties, controversies, and differing recommendations make the rationale for prolonged opioid use in CNCP unclear. This systematic review and meta-analyses compared the efficacy, safety, and tolerability of strong opioids with placebo or nonopioid therapy in CNCP, with a special focus on chronic low back pain (CLBP). Systematic literature searches were performed in 4 electronic databases (MEDLINE, Web of Science, Cochrane Library, and CINAHL) in July 2019 and updated by regular alerts until December 2020. We included 16 placebo-controlled randomized controlled trials for CLBP and 5 studies (2 randomized controlled trials and 3 nonrandomized studies) of opioids vs nonopioids for CNCP in the quantitative and qualitative synthesis. Random effects pairwise meta-analyses were performed for efficacy, safety, and tolerability outcomes and subgroup analyses for treatment duration, study design, and opioid experience status. Very low to low certainty findings suggest that 4 to 15 weeks (short or intermediate term) opioid therapy in CLBP (compared with placebo) may cause clinically relevant reductions in pain but also more gastrointestinal and nervous system adverse events, with likely no effect on disability. By contrast, long-term opioid therapy (≥6 months) in CNCP may not be superior to nonopioids in improving pain or disability or pain-related function but seems to be associated with more adverse events, opioid abuse or dependence, and possibly an increase in all-cause mortality. Our findings also underline the importance and need for well-designed trials assessing long-term efficacy and safety of opioids for CNCP and CLBP.